Hey, I Just Did a New Operation!. Issue 1 (January 2015) - Sagar, Stephen P.; Law, Peggy W.; Shaul, Randi Zlotnik; Héon, Elise; Langer, Jacob C.; Wright, James G.
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is Available in the Text.The safe introduction of surgical innovations is a key process for academic health sciences centers. Here, we describe the outcome of one type of formal policy that facilitated the transparent and monitored introduction of new procedures into a hospital setting.